2014
DOI: 10.15578/iaj.9.2.2014.97-102
|View full text |Cite
|
Sign up to set email alerts
|

FLUCTUATING ASYMMETRY REFLECT THE GROWTH OF HYBRID GROUPER Epinephelus fuscoguttatus AND Epinephelus polyphekadion

Abstract: Fluctuating asymmetry has been widely used as a measure of developmental stability and as an indicator of individual fish growth. The present study compared fluctuating asymmetry in three bilateral meristic traits of F-1 hybrid between female Epinephelus fuscoguttatus and male Epinephelus polyphekadion and two F-1 pure parental progenies. The fishes were reared by communal and separate tank systems. Hybrids were confirmed by allozymes electrophoresis. After three months of rearing, the F-1 hybrids fish grew fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
5
0
2
Order By: Relevance
“…The main appeal of hybrid groupers is in their increased growth rates. A recent evaluation of the E. fuscoguttatus 9 E. polyphekadion hybrid concluded that it grows 46% and 67% larger compared to F1 pure parental progenies of E. fuscoguttatus and E. polyphekadion, respectively, and the hybrid shows greater development stability than either F1 parental progeny (Sugama et al 2014). A major focus of research on hybrids has been to incorporate the rapid growth rate of E. lanceolatus in the genome of the hybrid.…”
Section: Genetics and Hybridisationmentioning
confidence: 99%
“…The main appeal of hybrid groupers is in their increased growth rates. A recent evaluation of the E. fuscoguttatus 9 E. polyphekadion hybrid concluded that it grows 46% and 67% larger compared to F1 pure parental progenies of E. fuscoguttatus and E. polyphekadion, respectively, and the hybrid shows greater development stability than either F1 parental progeny (Sugama et al 2014). A major focus of research on hybrids has been to incorporate the rapid growth rate of E. lanceolatus in the genome of the hybrid.…”
Section: Genetics and Hybridisationmentioning
confidence: 99%
“…designate as TGGG, noting that it is also popularly known as the Sabah grouper. 3 While hybridization improves the growth rate of groupers, 2,4 optimal production is dependent on appropriate physico-chemical properties of the culture environment and optimum nutrition. Feeds represent the largest individual cost input for seacage aquaculture and the conversion of feed to fish (feed conversion ratio, FCR) has been identified as a major driver of economic and environmental impacts of seacage operations.…”
mentioning
confidence: 99%
“…Hasil pemeliharaan benih kerapu hibrida cantik, macan, dan batik menunjukkan pertumbuhan dan sintasan benih kerapu cantik lebih baik dibandingkan dengan ikan kerapu macan dan batik pada pemeliharaan baik secara terpisah maupun komunal. Sugama et al (2014) menyatakan bahwa ikan kerapu hibrida mempunyai tingkat fluktuasi asimetri yang lebih rendah dibandingkan dengan ikan kerapu macan dan batik sehingga mempunyai stabilitas perkembangan yang lebih baik dan berkaitan erat dengan pertumbuhan ikan. Hal ini sesuai dengan salah satu tujuan hibridisasi yaitu untuk meningkatkan laju pertumbuhan (Bartley et al, 2001).…”
Section: Bahasanunclassified
“…Ikan kerapu cantik merupakan hasil persilangan antara betina ikan kerapu macan dengan jantan kerapu batik yang membuktikan bahwa persilangan dapat meningkatkan nilai keragaman genetik. Sugama et al (2014) menyatakan bahwa heterozigositas tinggi diduga dapat menurunkan fluktuasi asimetri, sehingga ikan kerapu hibrida cantik memiliki pertumbuhan yang lebih baik dibandingkan dari benih dari kedua induk pembentuknya. Nilai heterosis benih kerapu hibrida cantik tidak dapat dihitung karena tidak dihasilkan benih hibrida resiproknya akibat pemeliharaan larvanya yang cukup susah.…”
Section: Bahasanunclassified